Use & Abuse of Socrates in Teaching - Rud, Anthony G. (Education Policy Analysis Archives, 1997)
The Greek philosopher Socrates is used as an example of a master teacher in in many contexts, from elementary school discussions, to college philosophy classes, to law school. I examine a number of current uses of Socratic teaching, and expose inconsistencies among them. I analyze critically recent practitioners of Socratic teaching, such as Mortimer Adler, and I consider how the celebrated primary teacher Vivian Gussin Paley enacts the Socratic legacy in a novel way. I argue that the misuse, or abuse, of the Socratic legacy occurs chiefly when his teaching is interpreted narrowly as a pedagogical technique devoid of context and irony.